Caracterização de identidade cultural em projeto gráfico de curta animação - MENDONÇA, Nikole Melo de (2020)
Brazilian entertainment animation is a product that stands out in national and international territory. Animations produced in Brazil began to be shown throughout territory regions, being exported to various countries, obtaining nominations and awards at major international festivals. In the context of the effervescent modernity by internet-based Information and communication technologies, the easy and fast access to increasingly volatile digital content are short-lived animations, as they need to convey a message quickly and concisely. In this scenario, the focus emerges for the expression of culturality in the graphic language of animations, given the importance of valuing cultural heritage. Considering the designer's task to transpose an identity to the product through visual language, this research aims to understand how to structure an animation graphic project to promote an animated narrative with expressiveness of cultural identity. With methodological basis structured in a qualitative research with exploratory-descriptive bias and, through an inductive approach, was proceed an observational and analytical research to identify graphic designs in the Brazilian animation "Irmão do Jorel", compiling elements on the narrative of cultural identity and analyzing the structuring of those. As a research contribution, it was possible to propose a set of 14 recommendations for structuring a graphic animation project to promote the narrative with a focus on cultural identity. The results pointed to a mapping of 32 resources arranged in 6 distinct groups between built environment and objects; geography and the natural environment; cultural and typical events; society; characterization and graphic styles, as insertion points of graphic elements in the narrative of culturality in an animation.